Ascent!: 1Key Stage 3 Science - Petheram,Louise; Routledge,Phil; Ryan,Lawrie (United Kingdom: Nelson Thornes, 2002)
This brand new series is focused on delivering custom materials which are designed and presented to meet the needs of enthusiastic and committed students. The resources cover Levels 5-8/EP, written at an average reading ability level, but with full and proper use of scientific terminology throughout.
Keywords: Grande-Bretagne; Great Britain Science Study and teaching (Secondary); Great Britain Sciences Étude et enseignement; Science Study and teaching